Retrograde transvenous lymphatic embolization for postoperative chylous ascites: A report of three cases and literature review - Morikawa, Kazuhiko (Radiol Case Rep, 2020)
Percutaneous transabdominal lymphangiography and embolization have been reported as useful approaches for intractable chylothorax or chylous ascites. However, they are often difficult to perform after extensive lymph node dissection because disruption of the antegrade lymphatic flow makes leaks identification difficult. When the leakage point cannot be identified or percutaneous transabdominal lymphangiography and embolization fail, a retrograde transvenous approach to the thoracic duct can be used instead. We report 3 cases of refractory chylous ascites after retroperitoneal operation or extensive lymph node dissection that was addressed by retrograde transvenous lymphatic embolization. In one case, a combination of retrograde transvenous lymphatic embolization, transcatheter sclerotherapy, and transcatheter embolization was used. These findings suggest that retrograde transvenous lymphatic embolization appears to be feasible and efficient for postoperative chylous ascites.